2014
DOI: 10.1017/s0950268814001174
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance in newly diagnosed adults in a rural prefecture of eastern China

Abstract: Little is known about HIV drug resistance (HIVDR) in newly diagnosed HIV-infected adults in eastern China where the HIV epidemic is spreading predominantly through sexual contact. During 2008-2011, newly HIV-diagnosed adults in Taizhou prefecture, Zhejiang province in eastern China were examined for HIVDR by amplifying and sequencing the HIV-1 pol gene. Of 447 genotyped participants, 53·7% were infected with CRF01_AE, 20·1% with CRF07_BC, 12·5% with subtype B, and 11·6% with CRF08_BC. Most of the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
2
2
1
Order By: Relevance
“…We found that the overall prevalence of primary DR was 4.0%. This prevalence was comparable to that of previous studies in China, which showed 3.8% TDR in China during 2004 and 2005 [Liao et al, 2010], 3.2% in Guangxi in 2013 , 2.7% in Taizhou prefecture during 2008-2011 [Hua et al, 2015], 4.9% among MSM in 19 provinces/cities in 2010 [Yang et al, 2013]. The prevalence of DR in our study which categorized as low level was similar to Southern Vietnam [Tanuma et al, 2014] and Malaysia [Ong et al, 2014] on the whole, but lower than those in North America and Western Europe where TDR rates were reported to be 13.6% and 6.8% during 2004 to 2006 [Rahim et al, 2009], respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the overall prevalence of primary DR was 4.0%. This prevalence was comparable to that of previous studies in China, which showed 3.8% TDR in China during 2004 and 2005 [Liao et al, 2010], 3.2% in Guangxi in 2013 , 2.7% in Taizhou prefecture during 2008-2011 [Hua et al, 2015], 4.9% among MSM in 19 provinces/cities in 2010 [Yang et al, 2013]. The prevalence of DR in our study which categorized as low level was similar to Southern Vietnam [Tanuma et al, 2014] and Malaysia [Ong et al, 2014] on the whole, but lower than those in North America and Western Europe where TDR rates were reported to be 13.6% and 6.8% during 2004 to 2006 [Rahim et al, 2009], respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This prevalence was comparable to that of previous studies in China, which showed 3.8% TDR in China during 2004 and 2005 [Liao et al, 2010], 3.2% in Guangxi in 2013 , 2.7% in Taizhou prefecture during 2008-2011 [Hua et al, 2015], 4.9% among MSM in 19 provinces/cities in 2010 [Yang et al, 2013]. The surveillance of TDR in China has particularly important public health significance owing to the limited resources of antiretroviral drugs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall prevalence of PDR among the studied samples was 6.9%, and PDR in three years between 2016-2018 achieved a moderate level (5%-15%) according to the WHO categorization method [ 33 ]. The HIVDR rate was higher than that of previous studies in Liangshan [ 44 ] and other regions in China [ 38 , 45 ]. However, the resistance rate was lower than those in Kenya and Mexico, where PDR rates were reported to be 21.9% and 15.5% [ 46 , 47 ], respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…Henan province) are subtype B[8] and the major subtype at southeastern and eastern coastal area is subtype 01_AE. [21, 34, 35] The variations in subtype distribution might be due to different transmission patterns and status of co-evolution between virus and population, which couldn’t be confirmed in this study. The main subtypes found at Urumqi and Liuzhou blood centers: CRF07_BC and CRF01_AE, were the same as in our previous REDS-II findings[10], which were also consistent with the subtype distributions among high-risks groups at these two regions[36, 37].…”
Section: Discussionmentioning
confidence: 60%